Topical vs Peribulbar Anesthesia: Comparison of Anterior Chamber Depth and the Resultant Visual Outcome After Phacoemulsification - Naik MP (Dove Medical Press, 2020)
Mayuresh P Naik,1 Harinder Singh Sethi,2 Amita Yadav2 1Department of Ophthalmology, H.I.M.S.R & H.A.H. Centenary Hospital, Alaknanda, New Delhi 110062, India; 2Department of Ophthalmology, V.M.M.C & Safdarjung Hospital, Ansari Nagar, New Delhi 110029, IndiaCorrespondence: Mayuresh P NaikDepartment of Ophthalmology, H.I.M.S.R & H.A.H. Centenary Hospital, Room No. 3 of Eye OPD, 1st Floor of OPD Building, Near GK-2, Alaknanda, New Delhi 110062, IndiaTel +91-8287344576Email mayureshpnaik@gmail.comPurpose: To compare anterior chamber depth and postoperative visual outcome in patients undergoing phacoemulsification under topical vs peribulbar anesthesia.Materials and Methods: Prospective, randomized, comparative observational study.Sample size: 110 eyes with 55 eyes each.Group I: Patients undergoing phacoemulsification under topical anesthesia.Group II: Patients undergoing phacoemulsification under peribulbar anesthesia.Once patients were selected, baseline a standard ophthalmic examination was done including best-corrected visual acuity (BCVA), refraction, IOP by NCT, anterior segment evaluation with slit lamp biomicroscopy, keratometry, axial length, and ACD measurement by IOL master. Post-operatively, the patients were reviewed at day 1, week 1, week 6 for the same parameters.Statistics:Quantitative variables: Paired and unpaired t-test.Qualitative variables: Chi square test.A P-value of < 0.05 was considered statistically significant.Results: Inter-group comparisons of post-operative change in ACD at 1-week post-op (P-value< 0.001) and 6-week post-op (P-value< 0.001) were statistically significant when compared to the pre-op values. The mean spherical equivalent in group I was 0.27± 0.26 d and that in group II was 1± 0.32 d at 1-week post-op. The mean spherical equivalent in group I was 0.23± 0.20 d, while that in group II was 0.85± 0.64 d at 6-week post-op. This difference was statistically significant both at 1-week post-op (P-value=0.002) and 6-week post-op (P-value< 0.001).Conclusion: Post-phacoemulsification, the ACD is more after peribulbar anesthesia as compared to topical anesthesia. Post-op refractive outcome is better with the use of topical anesthesia.Keywords: phacoemulsification, topical anesthesia, peribulbar anesthesia, ACD, MSE